Numerical Simulation of Dynamic Response Characteristics of Cutting Coal and Rock by a Roller Coal Cutter - Kesong Fan; Yutong Feng; Ruoyang Kong; Hua Wei; Wenlong Jiao; Chenghao Fu; Yunsen Zhou (Shock and Vibration)
Currently, the identification technology of rock-coal medium is not reliable and practical, so we cannot judge the cutting state of coal-winning machine in real time. Different dynamic responses over different medium types of rock-coal can indirectly reflect the physical and mechanical parameters of rock-coal. In this study, we establish the 3-D numerical model of cutting the rock and coal by the finite element numerical simulation software in which we obtain the whole process of numerical simulation of the roller cutting coal, mudstone, and sandstone, where different dynamic responses counterpart different types of rock and coal by means of numerical experiments. The results show that when the drum keeps the average speed of cutting coal and medium forward, the instantaneous speed which is close to the average speed will have a small jump. The average speed and the torque in the cutting process can be considered as good indices to evaluate the rock and coal types. The torque from high to low is as follows: sandstone, mudstone, and coal. The average speed from high to low is as follows: coal, mudstone, and sandstone. If the portion of rock is more, the torque is higher and the average speed is lower during cutting the roof foot. This research is helpful for identifying rock-coal medium types by using related instrument to record the dynamic responses of rock-coal medium types.